PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS NEARPOD UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI VIRUS DI KELAS X SMA NEGERI 5 PEMATANGSIANTAR - Siregar, Jesica Feronica; Silaban, Winarto; Sirait, Gloria (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This research is motivated by the use of learning media that has not been able to increase students' interest and learning outcomes in learning. This study aims to (1) Determine the feasibility test of nearpod-based interactive learning media on virus material. (2) Determine students' responses to nearpod-based interactive learning media on virus material. (3) Determine the effect of using nearpod-based interactive learning media on virus material in class X of SMA Negeri 5 Pematangsiantar. The study used the Research and Development (R&D) method with the ADDIE development model. The results of this study are: The validation results show an average feasibility percentage of 93% with a very feasible category, with details of design feasibility of 90%, content/material 92%, language 97%, and presentation 94%. Students' responses to nearpod-based interactive learning media on virus material by providing a questionnaire sheet obtained responses in the very good category, namely 88%. Based on student learning outcome data obtained through pre-test and post-test, nearpod-based interactive learning media has an influence on student learning outcomes. This is evidenced by the Sig. value. The two-tailed value is 0.000, indicating that the value is <0.05. Therefore, it can be concluded that Ho is rejected and Ha is accepted. Keywords: learning media; development; nearpod. Abstrak: Penelitian ini dilatarbelakangi oleh penggunaan media pembelajaran yang belum dapat meningkatkan ketertarikan dan hasil belajar peserta didik dalam pembelajaran. Penelitian ini bertujuan untuk (1) Mengetahui uji kelayakan media pembelajaran interaktif berbasis nearpod pada materi virus. (2) Mengetahui respon peserta didik terhadap media pembelajaran interaktif berbasis nearpod pada materi virus. (3) Mengetahui pengaruh penggunaan media pembelajaran interaktif berbasis nearpod pada materi virus dikelas X SMA Negeri 5 Pematangsiantar. Penelitian menggunakan metode Research and Development (R&D) dengan model pengembangan ADDIE. Hasil penelitian ini adalah Hasil validasi menunjukkan persentase kelayakan rata-rata sebesar 93% dengan kategori sangat layak, dengan rincian kelayakan desain 90%, isi/materi 92%, bahasa 97%, dan penyajian 94%. Respon peserta didik terhadap media pembelajaran interaktif berbasis nearpod pada materi virus dengan memberikan lembar angket diperoleh respon dengan kategori sangat baik yaitu 88%. Berdasarkan data hasil belajar siswa yang diperoleh melalui pre-test dan post-test maka media pembelajaran interaktif berbasis nearpod memiliki pengaruh terhadap hasil belajar siswa. Hal ini dibuktikan dengan nilai Sig. 2 tailed adalah 0,000 yang menyatakan nilai tersebut < 0,05. Maka dapat disimpulkan Ho ditolak dan Ha diterima. Kata kunci: media pembelajaran; pengembangan; nearpod.